Слов’янські мотиви у дослідженнях молодого історика (до біографії В.К. Піскорського) - Новікова, Є. (Сiверянський літопис, 2021)
Целью данного исследования является освещение малоизвестных фактов из биографии знаменитого ученого, исследователя истории Испании и Португалии средних веков и нового времени, доктора всеобщей истории, профессора В.К. Пискорского. Методологическую основу исследования составили принципы историографического анализа и синтеза, проблемно-хронологический, ретроспективный, сравнительный, а так же метод биографистики. Научную новизну исследования составляют не освещенные ранее аспекты творческого наследия В.К. Пискорского по истории, филологии, этнологии славянских народов. Выводы. В многогранном творчестве В.К. Пискорского прослеживается интерес к филологии, этнографии, нравам, истории и традициям ряда славянских народов. Большинство материалов, позволяющих исследовать этот аспект его творчества, хранятся в Московском государственном и в семейном архивах. Это выписки из материалов по истории Перяславля, о гетмане Юрии Хмельницком, об Александре І, а также записи исторических песен, услышанных Владимиром Пискорским от бабушки своей жены З.З. Пискорской, дочери крепостного крестьянина, впоследствии выкупившегося на волю. В своих исследованиях известный ученый обращал особенное внимание на характерные черты славян в контексте общего развития европейской цивилизации. В письмах из зарубежных командировок он неоднократно сравнивал Европу с Украиной (Малороссией) и подчеркивал большое сходство их исторического развития, нравов и традиций. The purpose of this study is to highlight little-known facts from the biography of the famous scientist, researcher of the history of Spain and Portugal in the Middle Ages and modern times, Doctor of General History, Professor V.K. Piskorsky. The methodological basis of the research was formed by the principles of historiographic analysis and synthesis, problem-chronological, retrospective, comparative, as well as the method of biography. The scientific novelty of the research lies in research of previously unknown aspects of the creative heritage of V.K. Piskorsky on the history, philology, ethnology of the Slavic peoples. Conclusions. In the multifaceted work of V.K. Piskorsky from the time of the Historical Society of Nestor the Chronicler, and then him as a teacher of history, his interest in philology, ethnography, customs, history and traditions of a number of Slavic peoples can be traced. Most of the materials that make it possible to study this aspect of his work are still stored in the archives (Moscow, as well as in the family archive). These are extracts from materials on the history of Periaslavl, about hetman Yuri Khmelnitsky, about Alexander I, and recordings of historical songs heard by Vladimir Piskorsky from his wife’s grandmother Z.Z. Piskorskaya, daughter of a serf peasant, who was later set free. In his researches the famous scientist paid special attention to the characteristic features of the Slavs in the context of the general development of European civilization. In his letters from foreign business trips he repeatedly compared Europe with Ukraine (Little Russia) and emphasized the greater similarity of their historical development, morals and traditions.